Sleeping Safely! A Quality Improvement Project to Minimize Nighttime Interruptions without Compromising Patient Care - Lee, Clifton C. (Pediatr Qual Saf, 2021)
Sleep is crucial for patients’ health but is often disrupted, slowing recovery and resulting in adverse health effects. This study identified whether passive vital sign checks (heart rate, respiratory rate, and pulse oximetry) and delayed routine morning laboratories in clinically stable pediatric patients minimized nighttime interruptions without compromising patient safety. METHODS: After developing the inclusion criteria using the Pediatric Early Warning Score, we enrolled eligible patients for the intervention. We assessed physician compliance through order entry and nursing compliance through recorded vital signs and timing of blood draws. Eligible patients received passive vital sign checks at 4 am with routine morning laboratories drawn at midnight or 6 am, instead of 4 am, to minimize patients’ nighttime interruptions. All other nursing duties continued with the institution’s patient care policies. Finally, retrospective chart reviews were performed to determine whether the intervention resulted in the escalation of care, our primary outcome. RESULTS: We collected 2,138 individual data points, which represented approximately 420 patients. Over the intervention period, high compliance rates with physician order placement, nurse performing passive vital signs, and delayed blood draws were maintained. On eligible patients, there was no escalation of care or rapid response team involvement. CONCLUSIONS: The use of passive vital sign checks on eligible pediatric patients was generally well-received and had high compliance during the intervention period. There were no negative patient care consequences, supporting the feasibility of this program. Further studies are needed to determine sleep quality and patient satisfaction.